The Effect of Giardia Lamblia Infection on the Host Immunity and Inflammatory Cytokines - Abdulrazzaq , Alaa Abduljabbar; Jumaah , Yasameen Hasan; Ismael , Shahad Basil (American Journal of Biology and Natural Sciences, 2025)
The Giardia lamblia is an intestinal parasites in humans, it's a flagellate protozoan that lives in the host's upper small intestine. The tissue damage results from the parasite G. lamblia adhering toward the gut, this activate the host's immune system, which releases the chemicals and slow down the adsorption of nutrient. A persistent infection may have an impact on the immune cell population, such as increasing the number of T lymphocytes and encouraging an alternative immunological response. When compared to healthy controls, the increase in MN cells cultivated with raised levels of TNF-a, IL-2, IL-4, and IL-10 exhibited the highest activity, suggesting that these interleukins play a significant role in Giardia lamblia infection.